2013
DOI: 10.5578/tt.6208
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and properties of REM related obstructive sleep apnea among the patients with mild related obstructive sleep apnea

Abstract: ÖZET Hafif obstrüktif uyku apneli hastalarda REM ile ilişkili obstrüktif uyku apne sıklığı ve özellikleri GİRİŞObstrüktif uyku apne (OUA); üst hava yolunda tekrarlayan tıkanmalarla karakterize, erişkin popülasyonun %2-4'ünü etkileyen uykuyla ilişkili solunum hastalıkları-nın yaygın bir formudur. Uyku sırasında üst hava yolunda gelişen tıkanıklıkların hipoksemi, hiperkapni, otonomik sinir sistemi değişiklikleri ve uykuda bölünmeye yol açması OUA patofizyolojisinde belirleyicidir (1). REM ile ilişkili OUA ise ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
2
0
0
1
Order By: Relevance
“…( 13 ) In another study, similar to the present study, REM-related OSA was found to be more common in patients with moderate OSA than in those with severe OSA. ( 14 ) That is in agreement with our findings that the AHI values were lower in the patients with REM-related OSA than in those with NREM-related OSA (the initial phase of REM-related OSA in the literature), ( 15 ) and that the prevalence of REM-related OSA was higher among the women in our sample.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…( 13 ) In another study, similar to the present study, REM-related OSA was found to be more common in patients with moderate OSA than in those with severe OSA. ( 14 ) That is in agreement with our findings that the AHI values were lower in the patients with REM-related OSA than in those with NREM-related OSA (the initial phase of REM-related OSA in the literature), ( 15 ) and that the prevalence of REM-related OSA was higher among the women in our sample.…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have shown that NREM-related OSA is more common among patients with high AHI values (≥ 30 events/h). ( 15 - 17 ) Oksenberg et al ( 18 ) reported that, of their patients with NREM-related OSA, 49.1% had severe OSA, similar to the 48.1% observed in our study. The effects that high NREM-AHI values (due to subnormal REM sleeping times) and sleeping in the supine position had on the overall AHI values were large, because NREM occupies a majority of the sleep time, even under normal conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation